Student Search: The Study of Ethics Educational Leadership Management - Suriyadi Suriyadi; Bismar Sibuea; Suardi Suardi; Amiruddin Siahaan; Inom Nasution (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Student Search is often interpreted as